Pembingkaian Berita Pendeportasian Ustaz Abdul Somad dari Singapura dalam Tribunnews.com - Afryansyah, Afryansyah; Fitriani, Yessi; Effendi, Darwin (IAIN Padangsidimpuan, 2024)
This study aims to describe the framing and find out the ideology of Tribunnews.com in the news of the deportation of Ustaz Abdul Somad from Singapore as seen from the syntactic, script, thematic, and rhetorical structures. To achieve this goal, a descriptive linguistic method was used with a constructivism paradigm and analyzed using the Pan and Kosicki framing analysis model. The research data is in the form of 11 UAS deportation news on Tribunnews.com which were published from 17-26 May 2022 and were selected according to certain criteria. The results of the study show that out of eleven UAS deportation news on Tribunnewews.com, there is one pro-Government of Indonesia news, two pro-Singapore news, two pro-Singapore news, five pro-UAS news, and one objective news. This alignment is carried out by journalists by utilizing framing tools, namely through syntactic structures, script structures, thematic structures, and rhetorical structures. Tribunnews.com represents its ideology by siding with UAS as well as against Singapore.